2022
DOI: 10.1186/s12877-022-02977-w
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an intervention to reduce use of antibiotics for suspected urinary tract infection in nursing homes – a qualitative study of barriers and enablers based on Normalization Process Theory

Abstract: Background Overuse of antibiotics in the elderly population is contributing to the global health problem of antibiotic resistance. Hence, it is important to improve prescribing practices in care facilities for elderly residents. In nursing homes, urinary tract infection (UTI) is the most common reason for antibiotic prescription but inappropriate prescriptions are frequent. In order to reduce the use of antibiotics for suspected urinary tract infection in this context, a complex intervention ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…We have described an AMS intervention targeted at nursing and personal care staff. A recent systematic review reports that interventions to improve prescribing in aged care typically target physicians and nursing staff,27 with interventions targeting nurses and personal carers less commonly reported 17 28. A Danish study introducing education sessions and reflection and communication tools for nurses and nursing assistants reported positive qualitative (staff behaviour change in performing clinical assessments)17 and quantitative (reduced antibiotic prescribing for UTI) outcomes 28.…”
Section: Discussionmentioning
confidence: 99%
“…Interview guides (online supplemental files 1 and 2) were informed by the TDF domains13 and literature reviews 10 16–18. Overall content was not restricted by TDF to allow for the emergence of unanticipated topics during the interviews 19.…”
Section: Methodsmentioning
confidence: 99%
“…In case a positive impact is demonstrated, training and guidelines must be available, for example to improve asymptomatic bacteriuria management (Gahr et al., 2007), and reduce overtesting of residents for urine samples (Crnich et al., 2015). A Danish study suggested that a combination of educational activities and support tools can help nursing home nurses implement more evidence‐based practices regarding antibiotics for urinary tract infections in nursing homes (Kousgaard et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(Crnich et al, 2015). A Danish study suggested that a combination of educational activities and support tools can help nursing home nurses implement more evidence-based practices regarding antibiotics for urinary tract infections in nursing homes (Kousgaard et al, 2022).…”
Section: Itemsmentioning
confidence: 99%